2023
DOI: 10.1002/jmv.28672
|View full text |Cite
|
Sign up to set email alerts
|

The origin and evolution of emerged swine acute diarrhea syndrome coronavirus with zoonotic potential

Abstract: Swine acute diarrhea syndrome coronavirus (SADS‐CoV) is a newly discovered alphacoronavirus with zoonotic potential that causes diarrhea and vomiting mainly in piglets. Having emerged suddenly in 2017, the prevailing opinion is that the virus originated from HKU2, an alphacoronavirus whose primary host is bats, and at some unknown point achieved interspecies transmission via some intermediate. Here, we further explore the evolutionary history and possible cross‐species transmission event for SADS‐CoV. Coevolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Although the scale of outbreaks caused by this virus has not yet reached pandemic levels, it is still endemic to specific regions. Studies have consistently shown that SADS-CoV, with its unique structure, is at risk of evolving into a zoonotic virus [24][25][26]. The study of SADS-CoV is critical for the surveillance and control of animal diseases, while also enhancing our understanding of coronaviruses by identifying their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Although the scale of outbreaks caused by this virus has not yet reached pandemic levels, it is still endemic to specific regions. Studies have consistently shown that SADS-CoV, with its unique structure, is at risk of evolving into a zoonotic virus [24][25][26]. The study of SADS-CoV is critical for the surveillance and control of animal diseases, while also enhancing our understanding of coronaviruses by identifying their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…CUB is known to have a signi cant impact on a wide range of cellular processes such as mRNA stability, transcription, translation e ciency and accuracy, as well as protein structure, folding, expression, and function. Additionally, there are various practical applications in understanding CUB that are of signi cant value, including heterologous gene expression [19], identifying species origins [6,20], designing degenerate primers [21], predicting gene expression levels [22][23], predicting gene functions [24][25], and designing synthetic genes for biotechnological applications [26]. However, most of the numerous studies on CUB have focused on bacterium, fungi, viruses, and mycoplasma [27][28][29][30][31].…”
mentioning
confidence: 99%